Online OBE-CQI tool for engineering programmes / Mohaiyedin Idris, Mohd Affandi Shafie and Liaw Shun Chone - Liaw, Shun Chone (Universiti Teknologi MARA, Pulau Pinang & Pusat Penerbitan Universiti (UPENA), 2013)
In Malaysia, the Engineering Accreditation Council (EAC) has directed all engineering programmes especially at tertiary institutions to apply and implement outcome based education (OBE) in their teaching and learning system. One of the elements in the implementation of OBE is monitoring of the continuous quality improvement (CQI) of the courses every semester. Presently, the delivery format of the CQI reporting in most universities mainly uses close-loop method which is very much paper-based. The effect of using paper-based task in the process of gathering and filling information for CQI reporting purpose is a long and tedious one. This long process would incur time wastage, disorganisation and confusion in the data collection, sharing process and security of the documents. Based on these issues, an online OBE-CQI tool has been designed whereby the usage of client (instructor)-server method is to enable the instructor to transfer the details of CQI content into the server via network. Besides the interaction between server and instructor, the graphical user interface (GUI) is designed as a component to control all activities of filing the details of the CQI report such as CQI-Authorised, CQI-Possible Issue, CQI-Possible Solution, COs and POs overall marks score. From the results obtained by implementing the system (tools), all the CQI information stored in digital format becomes more systematic and easily accessible anytime in the network.